MirrorSAR: An HRWS Add-On for Single-Pass Multi-Baseline SAR Interferometry - Mittermayer, Josef; Krieger, Gerhard; Bojarski, Allan; Zonno, Mariantonietta; Villano, Michelangelo; Pinheiro, Muriel; Bachmann, Markus; Buckreuss, Stefan; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2022)
This article reports the Phase A study results of the interferometric extension of the high-resolution wide-swath (HRWS) mission with three MirrorSAR satellites. According to the MirrorSAR concept, small, low-cost, transponder-like receive-only satellites without radar signal demodulation, digitization, memory storage, downlink, and synchronization are added to the planned German X-band HRWS mission. The MirrorSAR satellites fly a triple helix orbit in close formation around the HRWS orbit and span multiple single-pass interferometric baselines. A comprehensive system engineering and performance analysis is provided that includes orbit formation, MirrorLink, Doppler steering, antenna pattern and swath design, multi-static echo window timing, SAR performance, height performance, and coverage analysis. The overall interferometric system design analysis of Phase A is presented. The predicted performance of the global digital elevation model (DEM) is improved by one order of magnitude compared to presently available global DEM products such as the TanDEM-X DEM.
Created from Fastlane, Scopus look-up
Keywords: Digital elevation model (DEM); high-resolution wide-swath (HRWS); interferometry; mirrorSAR; synthetic aperture radar (SAR)